The Impact of Socioeconomic Factors on Kidney Transplantation: A Systematic Review of Low- and Middle-Income Countries - Nguyen Xuong Duong; Minh Sam Thai; Ngoc Sinh Tran; Khac Chuan Hoang; Quy Thuan Chau; Xuan Thai Ngo; Trung Toan Duong; Tan Ho Trong Truong; Hanh Thi Tuyet Ngo; Dat Tien Nguyen; Khoa Quy; Tien Dat Hoang; et al. (Société Internationale d’Urologie Journal)
Kidney transplantation (KT) is a preferred treatment for end-stage renal disease (ESRD) because it offers better long-term survival and cost-effectiveness compared to dialysis. Significant global disparities persist in access to KT, particularly in low- and middle-income countries (LMICs). This study aims to assess the epidemiology and outcomes of KT in LMICs while examining the relationship between a country’s income level and its KT prevalence. A systematic review of the literature was conducted, with searches of PubMed, Scopus, and Web of Science from inception to 31 May 2024. Relevant articles reporting on the epidemiology and outcomes of KT or ESRD patients undergoing kidney replacement therapy (KRT) in LMICs were included. A total of 8054 articles were identified, with 972 articles selected for full-text screening after initial title and abstract review. Following full-text screening, 35 articles met the inclusion criteria. The data showed significant variation in KRT and KT prevalence across different geographical locations. Higher-income countries within LMICs tended to have higher KT prevalence rates. Barriers such as inadequate healthcare infrastructure, limited financial resources, and insufficient organ donation frameworks were identified as contributing factors to the low KT rates in these regions. The study highlights the disparities in KT access and prevalence in LMICs, underscoring the need for targeted interventions and international collaboration to address these gaps. Efforts to increase both living and deceased donor transplants, expand health system capacity, and incorporate KT in healthcare planning are needed to close this gap. Global partnerships spearheaded by organizations such as The Transplantation Society (TTS) and the International Society of Nephrology (ISN) are crucial for improving KT rates and outcomes in LMICs.